Rising drug allergy alert overrides in electronic health records: an observational retrospective study of a decade of experience. (17th November 2015) - Topaz, Maxim; Seger, Diane L; Slight, Sarah P; Goss, Foster; Lai, Kenneth; Wickner, Paige G; Blumenthal, Kimberly; Dhopeshwarkar, Neil; Chang, Frank; Bates, David W; Zhou, Li
Abstract : Objective There have been growing concerns about the impact of drug allergy alerts on patient safety and provider alert fatigue. The authors aimed to explore the common drug allergy alerts over the last 10 years and the reasons why providers tend to override these alerts. Design : Retrospective observational cross-sectional study (2004–2013). Materials and Methods Drug allergy alert data ( n = 611, 192) were collected from two large academic hospitals in Boston, MA (USA). Results Overall, the authors found an increase in the rate of drug allergy alert overrides, from 83.3% in 2004 to 87.6% in 2013 ( P < .001). Alarmingly, alerts for immune mediated and life threatening reactions with definite allergen and prescribed medication matches were overridden 72.8% and 74.1% of the time, respectively. However, providers were less likely to override these alerts compared to possible (cross-sensitivity) or probable (allergen group) matches ( P < .001). The most common drug allergy alerts were triggered by allergies to narcotics (48%) and other analgesics (6%), antibiotics (10%), and statins (2%). Only slightly more than one-third of the reactions (34.2%) were potentially immune mediated. Finally, more than half of the overrides reasons pointed to irrelevant alerts (i.e., patient has tolerated the medication before, 50.9%) and providers were significantly more likely to override repeated alerts (89.7%) rather than first time alerts (77.4%, P < .001). Discussion and Conclusions These findings underline the urgent need for more efforts to provide more accurate and relevant drug allergy alerts to help reduce alert override rates and improve alert fatigue.